Analisis Respon Orang Tua dan Strategi Guru terhadap Pembelajaran Berbasis Daring Pada Masa Pandemi Covid 19 - Ramadhan Prasetya Wibawa; Liana Vivin Wihartanti (Universitas PGRI Madiun, 2021)
This study aims to determine the response of parents and teacher strategies to online-based learning during the COVID-19 pandemic in Madiun City. This research uses descriptive quantitative method. The research sample was 60 students' parents and teachers. Data was collected using an online questionnaire via google form, while the data analysis technique was the percentage. The results of the study indicate that the response of parents to online learning is the facilities and infrastructure, the internet network is a factor supporting the smoothness of online learning. The teacher's strategy for online learning during the pandemic is through the teacher preparing lesson plans according to the existing curriculum and pandemic conditions, practical and innovative online learning media, the teacher then carries out an evaluation of the ongoing and already implemented learning